PENGARUH FOTO SELFIE TERHADAP KONSEP DIRI (STUDI KASUS MAHASISWA JURUSAN DAKWAH DAN KOMUNIKASI STAIN PAREPARE) - Fitriani Fitriani; Ahmad Sultra Rustan; Zulfah Zulfah (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2017)
This study uses a quantitative approach to instrument design quantitative correlation. The data collection techniques used in this study is a questionnaire. Data analysis technique used is descriptive and inferential statistical analysis. The theory used in this research is the theory of symbolic interaction, attribution theory and the theory of self-discloser. This is evidenced by analyzing data obtained from the results of a questionnaire of 100 respondents. The results obtained concerning the interpretation of data management value 0,0778≥ rtabel rhitung = 0.195. At the significant level of 5% then the alternative hypothesis is accepted